A Phenomena of Split Consiousness in the Lithuanian Vanguard Poetry of Early XX Century - Keturakis, Saulius (Sociologija. Mintis ir veiksmas, 2003)
The aim of the article is to analyze the relation of the vanguard with the social in the poetic texts of lithuanian varguard in the first decades of the twentieth century. The article develops the analysis of the texts on a level of tension between the writter as an artist and a citizen. The article argues that the spheres of aesthetics and social activity were being divided by the vanguard artists. While the artistic imagination was not constrained in the sphere of aesthetics, in the sphere of social activity the artists followed the societal models that defined a citizenship.